Disruptions in asymmetric centrosome inheritance and WDR62-Aurora kinase B interactions in primary microcephaly. - Sgourdou, Paraskevi; Mishra-Gorur, Ketu; Saotome, Ichiko; Henagariu, Octavian; Tuysuz, Beyhan; Campos, Cynthia; Ishigame, Keiko; Giannikou, Krinio; Quon, Jennifer L; Šestan, Nenad; Çağlayan, Ahmet O; Günel, Murat; et al. (Sci Rep, 2017)
Recessive mutations in WD repeat domain 62 (WDR62) cause microcephaly and a wide spectrum of severe brain malformations. Disruption of the mouse ortholog results in microcephaly underlain by reduced proliferation of neocortical progenitors during late neurogenesis, abnormalities in asymmetric centrosome inheritance leading to neuronal migration delays, and altered neuronal differentiation. Spindle pole localization of WDR62 and mitotic progression are defective in patient-derived fibroblasts, which, similar to mouse neocortical progenitors, transiently arrest at prometaphase. Expression of WDR62 is closely correlated with components of the chromosome passenger complex (CPC), a key regulator of mitosis. Wild type WDR62, but not disease-associated mutant forms, interacts with the CPC core enzyme Aurora kinase B and staining of CPC components at centromeres is altered in patient-derived fibroblasts. Our findings demonstrate critical and diverse functions of WDR62 in neocortical development and provide insight into the mechanisms by which its disruption leads to a plethora of structural abnormalities.
Keywords: Animals; Aurora Kinase B; Brain; Cell Cycle; Cell Differentiation; Cell Proliferation; Centrosome; Consanguinity; Disease Models, Animal; Epistasis, Genetic; Fluorescent Antibody Technique; Gene Expression; Humans; Inheritance Patterns; Male; Mice; Mice, Knockout; Microcephaly; Mutation; Nerve Tissue Proteins; Neural Stem Cells; Pedigree; Whole Genome Sequencing

Mutations in the Histone Modifier PRDM6 Are Associated with Isolated Nonsyndromic Patent Ductus Arteriosus. - Li, Na; Subrahmanyan, Lakshman; Smith, Emily; Yu, Xiaoqing; Zaidi, Samir; Choi, Murim; Mane, Shrikant; Nelson-Williams, Carol; Behjati, Mohaddeseh; Kazemi, Mohammad; Hashemi, Mohammad; Fathzadeh, Mohsen; et al. (Am J Hum Genet, 2016)
Nonsyndromic patent ductus arteriosus (PDA) is a common congenital heart defect (CHD) with both inherited and acquired causes, but the disease mechanisms have remained elusive. Using combined genome-wide linkage analysis and whole-exome sequencing (WES), we identified independent mutations in PRDM6, which encodes a nuclear protein that is specific to vascular smooth muscle cells (VSMC), has histone methyl transferase activities, and acts as a transcriptional suppressor of contractile proteins. In vitro assays showed that the mutations cause loss of function either by intracellular redistribution of the protein and/or by alteration of its methyltransferase activities. Wild-type embryonic ductus arteriosus (DA) exhibited high levels of PRDM6, which rapidly declined postnatally as the number of VSMCs necessary for ductus contraction increased. This dynamic change suggests that PRDM6 plays a key role in maintaining VSMCs in an undifferentiated stage in order to promote their proliferation and that its loss of activity results in premature differentiation and impaired remodeling of the DA. Our findings identify PRDM6 mutations as underlying genetic causes of nonsyndromic isolated PDA in humans and implicates the wild-type protein in epigenetic regulation of ductus remodeling.
Keywords: Cell Differentiation; Cells, Cultured; Ductus Arteriosus, Patent; Epigenesis, Genetic; Female; Fluorescent Antibody Technique; Histones; Humans; Immunoblotting; Male; Muscle Proteins; Muscle, Smooth, Vascular; Mutation; Pedigree; Transcription Factors

Somatic Mutations in NEK9 Cause Nevus Comedonicus. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; McNiff, Jennifer M; Antaya, Richard J; Choate, Keith A (Am J Hum Genet, 2016)
Acne vulgaris (AV) affects most adolescents, and of those affected, moderate to severe disease occurs in 20%. Comedones, follicular plugs consisting of desquamated keratinocytes and sebum, are central to its pathogenesis. Despite high heritability in first-degree relatives, AV genetic determinants remain incompletely understood. We therefore employed whole-exome sequencing (WES) in nevus comedonicus (NC), a rare disorder that features comedones and inflammatory acne cysts in localized, linear configurations. WES identified somatic NEK9 mutations, each affecting highly conserved residues within its kinase or RCC1 domains, in affected tissue of three out of three NC-affected subjects. All mutations are gain of function, resulting in increased phosphorylation at Thr210, a hallmark of NEK9 kinase activation. We found that comedo formation in NC is marked by loss of follicular differentiation markers, expansion of keratin-15-positive cells from localization within the bulge to the entire sub-bulge follicle and cyst, and ectopic expression of keratin 10, a marker of interfollicular differentiation not present in normal follicles. These findings suggest that NEK9 mutations in NC disrupt normal follicular differentiation and identify NEK9 as a potential regulator of follicular homeostasis.
Keywords: Adolescent; Adult; Child; Female; Fluorescent Antibody Technique; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation; Nevus; NIMA-Related Kinases; Prognosis; Skin Neoplasms; Young Adult

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome